Confiabilidade humana: uma abordagem baseada na análise ergonômica do trabalho na operação de um painel de equipamento - Silva, João Alexandre Pinheiro (2011)
The restructuring of production processes throughout the entire petrochemical chain brought impacts on the labor division, resulting in a series of new demands for knowledge and skills, which are added to old ones, in order to maintain the stability and reliability of the production system, under their responsibility. The objective of this thesis is to build a theoretical framework on human reliability and ergonomics as well as the observation and analysis of an oil refinery production system. It aims to identify conflicts and gaps between the strategies and actions developed by the operators as system reliability maintainance agents in their work daily routine, and the organizational managerial approach for human reliability in the company. In order to achieve these goals, the research approach adopted has the characteristics of literature review that encompasses bibliometrics and content analysis, mixing action research methodology and Ergonomic Workplace Analysis in field research. The literature review identified 304 articles about "human reliability in the ISI Web of Knowledge scientific basis, of which only 50 items are classified in the field of ergonomics (16%). The major research stream on human reliability focuses on nominal scenarios, and therefore, in the ergonomics point of view, focuses on the task, i.e., the prescribed work. Another research stream focus on the real work analysis. The Company studied has classical and a mechanistic point of view focuses on the errors identification and construction barriers through procedures, checklists and other prescription alternatives to improve performance in reliability area. It was evident the fundamental role of the worker as an agent of maintenance and construction of system reliability. There are several strategies adopted by operators to mitigate in practice the gap between prescribed and real work.